A General Equivalent Electrical Circuit Model for the characterization of MXene/graphene oxide hybrid-fiber supercapacitors by electrochemical impedance spectroscopy – Impact of fiber length. (1st February 2022) - Mainka, Julia; Gao, Wei; He, Nanfei; Dillet, Jérôme; Lottin, Olivier
Highlights: A transmission line model with Warburg impedance is needed to fit the spectra. The electrical resistance of the fibers governs the high frequency 45° line. The high frequency 45° line increases with the yarn length. Abstract: Performance engineering of electrochemical energy-storage devices such as Supercapacitors (SCs) requires updated modeling capable of characterizing their electrical output in unique device geometries. In this work, an Equivalent Electrical Circuit (EEC) is developed to fit the impedance data of pseudo-capacitive and electrostatic fiber-shaped supercapacitors (FSCs). The model is applied for the interpretation of impedance data measured on FSCs made of reduced Graphene Oxide (rGO) and MXene in the case of pseudo-capacitors and pure carbon in the case of Electrical Double-Layer Capacitors (EDLCs) as active electrode materials, and polyvinylalcohol (PVA) gel infiltrated with sulfuric acid as the electrolyte and separator. The FSC charge storage behavior is modeled using a Transmission Line Model (TLM) including a finite Warburg impedance for pseudo-capacitance, and a Constant-Phase Element (CPE) for the electrostatic contribution. The high frequency part of the Nyquist plots is characterized by a 45° straight line and the use of a TLM clearly improves the fit quality compared to a Randles circuit usually used for pseudo-capacitor modeling. The difference between the two ciruits becomes more visible as the length of the SC yarns increases, which is consistent with the observed increase in internal resistance with fiber length evidenced with the TLM. Furthermore, the fitting results indicate that the internal resistance of the TLM predominantly corresponds to the electrical resistance of the fiber, i.e. the electron conductive phase of the electrode, instead of the electrolyte ionic resistance in usual SCs. Finally, the low frequency part of the spectra is correctly modeled by a CPE without any leakage resistance, showing that self-discharge is not a significant issue for the electrostatic contribution, at least in the frequency range tested.